Pemanfaatan Sodium Alginat Dan Karbon Aktif Ampas Tebu Untuk Menurunkan Kadar Besi (Fe) Dan Mangan (Mn) Pada Air Sumur Bor - Nasution, Annisa Wulan Dhari; Daulay, Abdul Halim; Jumiati, Ety (Fakultas Teknik UMSU, 2025)
Drilled well water contains heavy metals with high levels of iron (Fe) and manganese (Mn). This research aims to evaluate the successful use of sodium alginate and sugarcane bagasse activated carbon to reduce iron (Fe) and manganese (Mn) levels. The remediation method was successfully used to reduce iron (Fe) and manganese (Mn) levels in drilled well water. The quality of the activated carbon used has been tested and meets the SNI 06-3730-1995 quality standards. The remediation process was carried out with five composition variations used in this research, namely Sample A (SA 5% : KAAT 95%), Sample B (SA 15% : KAAT 85%), Sample C (SA 25% : KAAT 75%), Sample D (SA 35% : KAAT 65%), and Sample E (SA 45% : KAAT 55%). The results of this research show that the combination of activated carbon with bagasse is able to reduce iron (Fe) and manganese (Mn) levels significantly, with the best results in reducing iron and manganese levels found in sample C, namely with iron (Fe) levels of 89.72% and manganese (Mn) content of 99.82%. Based on the analysis results, this method was proven to be effective in reducing iron and manganese levels.